THE ROLE OF UNPERBA’ SOCIAL MEDIA AS A DIGITAL MARKETING STRATEGY ON THE INTEREST OF STUDENTS’ ENROLLMENT - Afifah, Hana (Universitas Perwira Purbalingga, 2022)
The Role of UNPERBA’s Social Media As A Digital Marketing Strategy on The Interest Of Students’ Enrollment. The aim of this study is to examine the role of Universitas Perwira Purbalingga’s social media as a digital marketing strategy on the interest of students’ enrollment at Universitas Perwira Purbalingga (UNPERBA). The qualitative method approach was implemented in this study by appliying one on one interview with UNPERBA current students as the participants. The data was collected and interpreted verbatim with the number of participants was determined by the saturation. The result showed that UNPERBA’s social media is playing an important role for the potential students to seek detail information about UNPERBA before choosing to enroll. Thus, the participants give recommendation that UNPERBA need to post more about the students’ activities and Study Program activities to increase the interest of students’ enrollment.